2013
DOI: 10.1021/jp404698k
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Oxidation Study of Pt Nanoparticles on MgO(001)

Abstract: Noble metal nanoparticles supported by oxide carriers are widely employed in heterogeneous catalysis. In order to improve catalyst efficiency it is important to understand oxidation processes on the atomic scale. Here we studied oxygen-induced shape changes of Pt nanoparticles on MgO(001) by means of in-situ surface x-ray diffraction (SXRD) and x-ray reflectivity measurements (XRR). The x-ray results on the particle morphology were complemented by transmission electron microscopy (TEM) studies. The samples wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 84 publications
3
24
0
Order By: Relevance
“…A more plausible explanation is that increasing the O 2 /C 3 H 8 ratio from 5 to 20 results in the formation of a different oxide phase which interacts differently with CO. This hypothesis is supported by a wide body of literature which indicates that there are many types of platinum oxides that are formed on the surface of platinum nanoparticles during oxidation reactions-including PtO [51,52], Pt 3 O 4 [53,54], PtO 2 [51,[53][54][55][56][57], and subsurface oxide [14,16,46]-and the formation of these oxides depends on a number of factors including the oxygen coverage. For example, it has recently been shown that oxide growth on Pt(111) proceeds through several phase transitions with increasing oxygen coverage [19].…”
Section: Drifts Of Adsorbed Comentioning
confidence: 83%
See 2 more Smart Citations
“…A more plausible explanation is that increasing the O 2 /C 3 H 8 ratio from 5 to 20 results in the formation of a different oxide phase which interacts differently with CO. This hypothesis is supported by a wide body of literature which indicates that there are many types of platinum oxides that are formed on the surface of platinum nanoparticles during oxidation reactions-including PtO [51,52], Pt 3 O 4 [53,54], PtO 2 [51,[53][54][55][56][57], and subsurface oxide [14,16,46]-and the formation of these oxides depends on a number of factors including the oxygen coverage. For example, it has recently been shown that oxide growth on Pt(111) proceeds through several phase transitions with increasing oxygen coverage [19].…”
Section: Drifts Of Adsorbed Comentioning
confidence: 83%
“…On the contrary, several experimental studies [18,46,50,53,54,60] show that platinum oxides are inactive for CO oxidation near room temperature. The structure of the low activity oxides has been identified as PtO 2 [53,54,60] and Pt 3 O 4 [53], which were also the oxide phases identified as highly reactive. These contradictions regarding the catalytic activity of platinum oxides indicate that there are significant differences in the catalytic activity of platinum oxides, but also that the catalytic activity of platinum oxides is not well understood.…”
Section: Platinum Oxide Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface-sensitive x-ray diffraction (SXRD) allows a quantitative determination of the atomic structure of truncated realspace objects with internal periodicity, such as single crystals or crystalline faceted nanoparticles, exhibiting well-defined surfaces and interfaces [1][2][3][4][5][6][7]. Because of the compatibility of x-ray diffraction experiments with harsh sample environments, such as elevated temperatures, reactive gas mixtures at atmospheric pressures, or strong electromagnetic fields, in the last decade SXRD has opened unique opportunities for the investigation of surfaces and nanostructures under application relevant conditions [8][9][10][11][12][13][14][15]. In the case of single crystals, the surface structures are retrieved from the analysis of intensity variations along sets of crystal truncation rods (CTRs), which are lines in reciprocal space of nonzero diffracted intensity oriented perpendicular to the respective surface and interconnecting the corresponding Bragg peaks of the bulk material.…”
Section: Introductionmentioning
confidence: 99%
“…To measure the integrated intensities at various points along the CTRs, the sample needs to be rotated in the traditional SXRD rocking-scan mode (E = 10−20 keV) around its surface normal at each point ("rocking scan" [4]), which is, however, rather time-consuming (on the order of hours or days for a complete set). For epitaxial nanoparticles supported by single-crystalline substrates, extended reciprocal-space maps need to be recorded, which can be simulated to retrieve the average nanoparticle shape and size [11][12][13]. They also involve time-consuming sample and detector movements.…”
Section: Introductionmentioning
confidence: 99%